Physiological reactions to long-term fishing in the Barents Sea. (10th February 2018) - Netterstrøm, B; Hansen, Å M; Isaacson, D; Simonsen, A M; Weihe, P
Abstract: Background: Fishing in distant waters for months may induce physiological stress. Aims: To assess the physiological stress reactions in fishermen working for 2–3 months continuously in 6-h shifts on trawlers in the Barents Sea. Methods: The crew of five trawlers fishing in the Barents Sea from January to April 2004 were invited to participate. In the week before and 5–7 days after the trip, the following measures were collected: salivary cortisol four times a day, 24-h urinary cortisol, blood pressure, heart rate, serum cholesterol, serum high-density lipoprotein (HDL-cholesterol), HbA1c (glycosylated haemoglobin) and weight. In addition, 24-h urinary cortisol, blood pressure and heart rate were measured three times. A questionnaire on health, social conditions and work environment was obtained after the trip. Results: In total, 136 men agreed to participate. Full data were obtained for 96 fishermen (70%). A significant decrease in salivary and urinary cortisol was found during the trip. Adjustment for age, body mass index, smoking, shift work schedule and time of day for sample collection did not change this finding. Systolic and diastolic blood pressure declined significantly and remained significantly lower after the trip compared to before the trip. Serum cholesterol/HDL ratio declined significantly, whereas triglycerides, HbA1c and weight were unchanged. Conclusions: Working up to 3 months on 6-h shifts, 84 h a week, with moderate physical activity, even in artificial light and cold weather on a ship, did not result in increased physiological stress.